Serotonin release mediates analgesia via opioidergic system and withdrawal symptoms in chronic kratom extract-treated mice - Dwi Wahyu Indriani; Siti Irma Rahmawati; Asep Bayu; Peni Ahmadi; Anissa Nofita Sari; Zuraida Zuraida; Ni Luh Putu Indi Dharmayanti; Masteria Yunovilsa Putra (BMC Complementary Medicine and Therapies)
Abstract Background Kratom alleviates pain by activating μu-opioid receptors (MOR), which trigger serotonin release to produce analgesia. Serotonin also interferes drug abuse effect. This study aimed to determine the role of serotonin in kratom-induced pain relief and withdrawal symptoms in mice. Methods The analgesic effect was assessed using the hot-plate test. To induce withdrawal symptoms, mice received naloxone after being treated with kratom extracts for five days at increasing doses. Another group of morphine-dependent mice was treated with kratom extracts to ameliorate their withdrawal symptoms. A molecular docking study and molecular dynamics were conducted to predict the binding target of alkaloid kratom for increasing serotonin levels. Results Chronic administration of kratom alkaloid extract (20 mg/kg) produced analgesic effects comparable to morphine (10 mg/kg). In contrast, kratom crude extracts (10 mg/kg and 20 mg/kg) demonstrated lower analgesia activity. This analgesic effect was mediated by MOR activation, leading to decreased intracellular cAMP and increased serotonin transmission. Repeated and increasing doses of crude or alkaloid kratom extracts (8 mg/kg to 45 mg/kg) produced less severe withdrawal symptoms than morphine. Increased dopamine and serotonin levels contributed to the onset of withdrawal symptoms. In the morphine group, treatment with kratom extracts increased serotonin levels while reducing dopamine. Molecular docking and molecular dynamics result revealed that kratom alkaloids interacts more readily with tryptophan hydroxylase, the enzyme responsible for serotonin biosynthesis. Conclusions Kratom extracts have the potential to provide analgesic effects and withdrawal symptoms, both of which are mediated by elevated serotonin release.